Attractive mechanical properties of a lightweight highly sensitive bi layer thermistor: polycarbonate/organic molecular conductor. Issue 1 (January 2016) - Laukhina, E; Lebedev, V; Rovira, C; Laukhin, V; Veciana, J
Abstract: The paper covers some of the basic mechanical characteristics of a recently developed bi layer thermistor: polycarbonate/(001) oriented layer of organic molecular conductor α'-(BEDT-TTF)2 Ix Br3-x, were BEDT-TTF=bis(ethylenedithio)tetrathiafulvalen. The nano and macro mechanical properties have been studied in order to use this flexible, low cost thermistor in sensing applications by proper way. The nano-mechanical properties of the temperature sensitive semiconducting layer of α'-(BEDT-TTF)2 Ix Br3-x were tested using nanoindentation method. The value of Young's modulus in direction being perpendicular to the layer plan was found as 9.0 ±1.4 GPa. The macro mechanical properties of the thermistor were studied using a 5848 MicroTester. The tensile tests showed that basic mechanical characteristics of the thermistor are close to those of polycarbonate films. This indicates a good mechanical strength of the developed sensor. Therefore, the thermistor can be used in technologies that need to be instrumented with highly robustness lightweight low cost temperature sensors. The paper also reports synthetic details on fabricating temperature sensing e-textile. As the temperature control is becoming more and more important in biomedical technologies like healthcare monitoring, this work strongly contributes on the ongoing research on engineering sensitive conducting materials for biomedical applications.